Implementasi Algoritma Rot Dan Subtitusional Block Cipher Dalam Mengamankan Data - Pratiwi, Ayu (LPPM UNIKA Santo Thomas Medan, 2017)
The security and confidentiality of data is one of the most important aspects in the information system at this time. Caused by the rapid development of science and technology that allows the emergence of new techniques, which are misused by certain parties that threaten the security of information systems. In general, the data are categorized into two, namely confidential data and data that is not confidential. Data that is not confidential is usually not too much attention. What really needs to be considered is confidential data, where every information contained in it will be very valuable for those who need it because the data can be easily duplicated. The ROT-n algorithm is one simple encryption algorithm that uses alphabetical shifts as much as n to convert plain text into cipher text, whereas Block ciphers work by processing data in blocks, where several characters / data are combined into one block. Each one block process produces one block output as well.